Three-dimensional non-linear analyses of steel special moment resisting frames - Kiser, Sidney Renee (Kansas State University, 2020)
A special moment resisting frame (SMRF) is a type of lateral force resisting system that is used to protect structures from extreme seismic events. This report evaluates the performance of a steel SMRF with an emphasis on the lower story elements. Previous research evaluating the performance of a reinforced concrete SMRF concluded that two-dimensional finite element analyses (2D-FEA) and three-dimensional finite element analyses (3D-FEA) have varying results. These varying results were so extreme in two instances that a change in design standards and codes was deemed necessary. In order to determine if the same conclusions can be drawn when analyzing a steel SMRF, this report used 2D-FEA and 3D-FEA programs to analyze a steel SMRF from Section 5.2 of the FEMA 451, NEHRP Recommended Provisions: Design Examples. The lower story member forces were gathered from both programs at 28 locations, then the percent difference was calculated. Analysis showed that the beam axial forces varied by more than 50 percent and that the beams varied in behavior. One form of analysis showed that the beams were undergoing axial compression while the other showed that the beams were experiencing axial tension. Upon discovering these differences, the beam axial forces were further studied by comparing the lower story beam displacements. The beam elongations differed by more than 1000 percent in some locations. These findings affirmed previous research by showing a large difference in 2D-FEA and 3D-FEA results. Though this research proved that the two forms of analyses vary greatly, this is only true of the axial forces. Even then, the variances equated to less than a hundredth of an inch. This variance is minimal in the overall scheme of design and it does not warrant a change in design standards, contrary to the reinforced concrete SMRF analyzed in previous research.
Keywords: finite element analysis; steel structure; steel special moment frame; non-linear analysis